2014
DOI: 10.1177/0907568214538290
|View full text |Cite
|
Sign up to set email alerts
|

“Cause it’s family talking to you”: Children acting as change agents for adult food and physical activity behaviors in American Indian households in the Upper Midwestern United States

Abstract: This article presents research findings from the formative phase of OPREVENT, a pilot obesity prevention intervention trial for American Indian households on two reservations in the Upper Midwestern United States. We describe processes by which American Indian children acting as change agents influence adult food and physical activity behaviors on an Ojibwa and a Potawatomi reservation. This study borrows from Bronfenbrenner and Ceci's socio-ecological model and extends Daniel's resiliency theory for practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 40 publications
3
36
0
Order By: Relevance
“…The current study findings are consistent with the concept of reciprocal determinism in that family members described influencing each other's knowledge about health, belief about their abilities to create change, and expectations of outcomes related to dietary or activity changes. Consistent with previous literature (Gadhoke et al, 2015;Laroche et al, 2008Laroche et al, , 2009Williams, et al, 2011), we found health approaches used by both adults and children were influenced by other family members, both in regards to diet and physical activity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current study findings are consistent with the concept of reciprocal determinism in that family members described influencing each other's knowledge about health, belief about their abilities to create change, and expectations of outcomes related to dietary or activity changes. Consistent with previous literature (Gadhoke et al, 2015;Laroche et al, 2008Laroche et al, , 2009Williams, et al, 2011), we found health approaches used by both adults and children were influenced by other family members, both in regards to diet and physical activity.…”
Section: Discussionsupporting
confidence: 91%
“…Children also have more direct influences on parents' diet and physical activity. Children can play active roles in being a part of and advocating for, change in diet and physical activity for parents with diabetes (Gadhoke, Christiansen, Swartz, & Gittelsohn, 2015;Laroche et al, 2009). Some parents may be motivated to be more physically active to be good role models for their children, to provide opportunities for their children to be physically active, or to stay healthy and be able to care for their children for the long term (Mailey, Huberty, Dinkel, & McAuley, 2014), possibly impacting their outcome expectations for being more active.…”
Section: Children's Influence On Parentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these data will help researchers and programme staff to identify potential ‘change agents’ (31) (i.e. influential individuals who could be engaged in obesity prevention interventions), as well as generate strategies to effectively incorporate social relationships in nutrition interventions.…”
mentioning
confidence: 99%
“…Children influence adults in their households positively for healthier nutrition and PA related habits on multiple levels [36–41]. School-based curricula have reported improved adult household members’ food getting habits, reduced fat intake and consumption, increased fruit and vegetable consumption, and lower BMI.…”
Section: Methodsmentioning
confidence: 99%